2010
DOI: 10.1111/j.1365-2672.2010.04896.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of Vitreoscilla haemoglobin in Sphingomonas elodea to improve gellan gum production

Abstract: Aims:  To improve a commercially used strain for gellan production by exogenous Vitreoscilla haemoglobin (VHb). Methods and Results:  VHb gene was expressed in Sphingomonas elodea under the control of constitutive bla promoter. Biochemical activity of expressed VHb was confirmed by CO‐difference spectra analysis that exhibited a characteristic absorption maximum at 419 nm. During cultivation, not only enhanced cell growth was detected, but also 20% improvement in gellan production was observed after 48 h of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Microbial exopolysaccharide (EPS) has a wide range of industrial (such as textiles, oil recovery, food additives, cosmetic and pharmaceutical) and medical applications. The collection of diverse products from different microorganisms include: xanthan from Xanthomonas [1], gellan from Sphingomonas [2], heparason from E. coli [3], glucans from Leuconostoc, Streptococcus and Lactobacillus [4], cellulose from Acetobacter [5], hyaluronan from Pseudomonas and Streptococci group A and C. In recent years there has been an increased interest in EPS for pharmaceutical applications such as antioxidants, antitumor agents and immunostimulants [6].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial exopolysaccharide (EPS) has a wide range of industrial (such as textiles, oil recovery, food additives, cosmetic and pharmaceutical) and medical applications. The collection of diverse products from different microorganisms include: xanthan from Xanthomonas [1], gellan from Sphingomonas [2], heparason from E. coli [3], glucans from Leuconostoc, Streptococcus and Lactobacillus [4], cellulose from Acetobacter [5], hyaluronan from Pseudomonas and Streptococci group A and C. In recent years there has been an increased interest in EPS for pharmaceutical applications such as antioxidants, antitumor agents and immunostimulants [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most zeaxanthin-producing organisms are unable to synthesize EPS. Sphingomonas species have been used to produce EPS. , Here, we showed that Sphingobium sp. could accumulate as high amounts of EPS as its relatives, Sphingomonas species.…”
Section: Resultsmentioning
confidence: 98%
“…However, inadequate oxygenation, resulting in poor cell growth and reduced product yields, is one major limitation encountered in large-scale bioreactors. Gellan production was reported to almost completely cease when the dissolved oxygen (DO) concentration was adjusted to zero [4]. Furthermore, the DO also played a critical role in the viscosity and molecular weight of the polymer produced, which was closely related to the rheological properties and applications of gellan gum.…”
Section: Introductionmentioning
confidence: 99%